THE OMISSIONS OF SENTENCE COMPONENT ON NEWS HEADLINES IN THE JAKARTA POST - Budiarto, Cisillia (Journal of English Department WM, 2014)
News headlines are the most noticeable feature in the newspapers. Readers are able to choose what kind of news that they want to know by reading the headlines. However, the forms of the headlines are unique and sometimes they are quite difficult to be understood since some words in the headlines are omitted in order to keep the headlines short. This study is conducted to find what sentence components in terms of phrase structure categories and syntactic categories are omitted. This study analyzes the Jakarta Post (Indonesia's leading English-language daily) headlines from online version syntactically using a tree diagram proposed by Marianne Celce â€“ Murcia and Diane Larsen â€“ Freeman (1999). The sources of the data are 81 headlines from national news section issued from November 1st to November 30th, 2013. In those headline, some words are omitted. The study finds that there are omissions in the Jakarta Post headlines which are under the phrase structure categories AUX, AUX + VP, NP, VP, AP, PREP P, and S. Out of these phrase structure categories, AUX and AUX + VP occur most frequently in the headlines with the percentage of 75% and 13% respectively. Under the syntactic categories, omissions which occur are T + 2 Passive, T + pm, T + prog, T + cop, conjunction, determiner and preposition. The omission of â€œbeâ€ in the syntactic categories T + Passive, T + pm, T + prog and T + cop occurs most frequently.